New species and nomenclatural notes in Acianthera from Brazil - Toscano de Bito, Antonio; Luer, Carlyle (Lankesteriana: International Journal on Orchidology, 2015)
Two new Brazilian species of the orchid genus Acianthera, Acianthera calopedilon and Acianthera cephalopodiglossa, are described and illustrated. The identities of Acianthera bidentula, Acianthera saundersiana, and Acianthera serpentula are discussed. Acianthera velteniana, recently described for Espírito Santo, is placed in the synonymy of Acianthera bidentula. An epitype is selected for Pleurothallis saundersiana and a lectotype for Pleurothallis serpentula. Updated synonymy lists are provided for the taxa treated in the article.